Relationship of X-RAY Images of Thorax Bronchopneumonia with Leucosytosis in Intensive Care Unit Patients in RSUD dr. Chasbullah Abdul Madjid Bekasi City - Utomo, Tranggono Yudo (Fakultas Kedokteran, Universitas Palangka Raya, 2022)
Bronchopneumonia is the most common picture of pneumonia found, especially in the ICU. Bronchopneumonia occurs due to the interaction between infection and cellular immunity which causes peribronchial consolidation. This process can result in leukocytosis in the patient. This research is an observational analytic study with a cross sectional method which was carried out in RSUD dr. Chasbullah Abdulmajid Bekasi City, West Java with secondary data from patient medical records in the period 1 November 2021 – 19 December 2021. Samples were taken using the total sampling method from population being treated at the ICU Cattleya. The variables taken were age, gender, the diagnosis to be taken, the results of a chest X-ray, and the value of the patient. The sample used was 101 patients. The most demographic characteristics were men at 49.5%, the 18-64 year group at 68.3%, and the basic diagnosis of ICU care for cerebrovascular disease was 24.8%. Statistical test using Chi-square test found that there was no relationship between bronchopneumonia and leukocytosis (p=0.172; p>0.05). This study showed that there was no association between chest x-ray bronchopneumonia and leukocytosis in ICU patients